2018
DOI: 10.2152/jmi.65.280
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Disorder and Early Media Exposure: Neurobehavioral symptoms mimicking autism spectrum disorder

Abstract: Many studies have reported many adverse effects of children's use of media. These effects include reduced cognitive development and hyperactivity and attention disorders. Although it has been recommended that child be kept away from the media during the early developmental period, many modern parents use the media as a way to calm their children. Consequently, these children lack the opportunity to form selective attachments by reduced social engagement. These children's symptoms occasionally mimic autism spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Another study by Chonchaiya et al found that ASD children began to watch television around six months earlier than typically developing peers [23]. In addition, several case reports indicated that young autistic-like children with heavy screen use were re-assessed as non-autistic after a couple months of screen media isolation [24,25]. However, far little attention has been paid to the development of autistic-like behaviors due to early childhood screen exposure, especially at age 0-3 years, when brain plasticity and neurobehavioral development are at their peak [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Chonchaiya et al found that ASD children began to watch television around six months earlier than typically developing peers [23]. In addition, several case reports indicated that young autistic-like children with heavy screen use were re-assessed as non-autistic after a couple months of screen media isolation [24,25]. However, far little attention has been paid to the development of autistic-like behaviors due to early childhood screen exposure, especially at age 0-3 years, when brain plasticity and neurobehavioral development are at their peak [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Although the long-term effects of digital devices such as smartphones and computers on infants have not yet been extensively investigated, studies showing the destructive effects of these devices on children's cognitive abilities, attention, behaviour and educational abilities are on the rise (Sadeghi et al, 2019). A case study found that children's extreme exposure to digital devices was associated with autistic-like symptoms (decreased eye contact, language delay and hyperactivity) and attachment problems (Numata-Uematsu et al, 2018). Due to insufficient development of attention and memory skills in the early years after birth, young children cannot learn from digital devices as much as interacting with adults, and it is difficult for them to transfer knowledge from digital devices to everyday life (Barr, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Wu and his team, in a Chinese study on 8900 children aged 3 to 6 years, showed the existence of an increased risk of total difficulties, emotional symptoms, conduct problems, hyperactivity, peer problems, and prosocial problems, as well as behavioral symptoms mimicking autism spectrum disorder, in children exposed to more than 2 h of television per day [ 13 ]. Moreover, Numata-Uematsu reported a 5-year old boy who, having been exposed to media during his early development, had later displayed neurobehavioural symptoms that mimicked autism [ 14 ]. Similar observations have been reported and discussed by clinicians worldwide [ 15 – 17 ].…”
Section: The Known Effects Of Traditional Media (Tv and Video)mentioning
confidence: 99%